(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The recognition of LGBTIQ+ rights has become one of the most transformative developments in contemporary constitutional democracies. In India, the movement for equality and dignity for sexual and gender minorities has evolved through judicial activism, constitutional interpretation, human rights advocacy, and social reform movements. The decriminalization of consensual same-sex relations in Navtej Singh Johar v. Union of India (2018) marked a historic constitutional milestone by partially invalidating Section 377 of the Indian Penal Code. However, despite this progressive development, marriage equality and broader civil rights for LGBTIQ+ individuals remain legally unrecognized in India. The denial of legal recognition to same-sex unions continues to deprive queer couples of numerous social, economic, and legal entitlements available to heterosexual couples. This article critically analyses the emerging legal trends and challenges relating to LGBTIQ+ rights and marriage equality in India. It examines the constitutional framework governing equality, dignity, liberty, privacy, and non-discrimination under Articles 14, 15, 19, and 21 of the Constitution of India. The paper also explores significant judicial pronouncements, including NALSA v. Union of India, Puttaswamy v. Union of India, Navtej Singh Johar v. Union of India, and Supriyo @ Supriya Chakraborty v. Union of India, which collectively shaped India’s queer rights jurisprudence. Further, the article analyses the legal consequences arising from the non-recognition of same-sex marriages, including issues relating to inheritance, adoption, guardianship, insurance, succession, taxation, and social security. Comparative legal perspectives from countries such as the United States, Canada, South Africa, Taiwan, and Nepal are also discussed to understand global trends in marriage equality jurisprudence. The article argues that while judicial recognition of sexual orientation and gender identity has significantly advanced constitutional morality in India, the absence of comprehensive anti-discrimination legislation and marriage equality continues to perpetuate structural discrimination. The paper concludes that achieving substantive equality for LGBTIQ+ persons requires legislative reform, inclusive family laws, public awareness, and a stronger commitment to transformative constitutionalism and human rights principles.